A clinical study of tramadol as an analgesic in labour - B., Shyamsundar; M. B., Vinutha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Labour is a painful event, may be the most painful event that women has even experienced. It is unpleasant disturbing and extremely unbearable for many. Methods: The clinical trial was conducted from July 2016 to June 2017 at Karnataka Institute of Medical Sciences, Hubballi. 200 parturients which included both primigravidae and multigravidae in labour at term were alternatively divided into two groups. The study group (n = 100) received 50mg-100mg of Tramadol and control group (n = 100) received no analgesic at the onset of active labour. Degree of pain relief, type of delivery, duration of labour, maternal and foetal morbidity were noted. Results: Pain relief in stage I was grade I (no pain) in 24% V/s 2%, grade II (mild pain) in 62% V/s 40%, grade III (moderate pain) in 13% V/s 56% and grade IV (severe pain) in 1% V/s 2% in study and control groups respectively (p < 0.001). Pain relief in stage II was grade I (no pain) in 8% V/s 0%, grade II (mild pain) in 47% V/s 7%, grade III (moderate pain) in 33% V/s 49% and grade IV (severe pain) in 12% V/s 43% in study and control groups respectively (p < 0.001). Duration of labour was significantly shorter in study group as compared to control group. There was minimal maternal morbidity in study group and no significant difference in the incidence of foetal morbidity in both the groups. Conclusions: Tramadol is an effective and safe labour analgesic. Besides it also shortens the duration of labour.